2003
DOI: 10.1002/ffj.1201
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents of the essential oil of the hornwort Anthoceros caucasicus

Abstract: The essential oil of the hornwort Anthoceros caucasicus (Bryophytae), collected on the island of Madeira, was investigated by gas chromatography, mass spectrometry and NMR techniques. A new sesquiterpene ether, veticadinoxide (1) was identified as the major constituent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Among these compounds, 4-dehydroviridifl orol, myliol and veticadinoxide are especially unusual sesquiterpenoids and were identifi ed by comparison of their mass spectra and retention indices with MassFinder 4 Library and published data. [14,15] It has been reported that 4dehydroviridifl orol and myliol are contained in the liverworts Mylia taylorii and Mylia nuda. [14] Veticadinoxide was fi rst identifi ed from the essential oil of the hornwort, Anthoceros caucasicus.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these compounds, 4-dehydroviridifl orol, myliol and veticadinoxide are especially unusual sesquiterpenoids and were identifi ed by comparison of their mass spectra and retention indices with MassFinder 4 Library and published data. [14,15] It has been reported that 4dehydroviridifl orol and myliol are contained in the liverworts Mylia taylorii and Mylia nuda. [14] Veticadinoxide was fi rst identifi ed from the essential oil of the hornwort, Anthoceros caucasicus.…”
Section: Resultsmentioning
confidence: 99%
“…Humidifi ed air was added in the sniffi ng port at 100 ml/min. Aroma-active compounds were identifi ed by comparing their mass spectra with the spectral data of MS libraries (NIST 02, MassFinder 4), published data [15][16][17][18] and our previous work. [6][7][8][9][10][11]…”
Section: Gas Chromatography-mass Spectrometry/olfactometry (Gc-ms/o)mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the diterpene found (in low quantities) is known for Anthoceros caucasicus Steph. (Sonwa & Köning, 2003). It is important to grow Leiosporoceros in axenic cultures to determine if the secondary metabolites it produces are, at least in part, the result of its association with its Nostoc endosymbiont.…”
mentioning
confidence: 99%
“…Presence of structurally different xyloglucans is noted in the cell wall of hornworts which is similar to vascular plants and differs from liverworts and mosses [164] . A sesquiterpene ether, veticadinoxide from Anthoceros caucasicus was reported [165] . Phytochemical analyses were performed in some other hornwort members such as Anthoceros agrestis [166][167][168][169] , Anthoceros caucasicus [170] , Megaceros flagellaris [171] , etc.…”
Section: Hornwortsmentioning
confidence: 99%